Research Analyst Forecasting Accuracy and Earnings Management: Evidence from Pakistan - Sajjad, Waseem; Yet, Chu EI; Hong, Meenchee; Asim, Muhammad (Journal of Entrepreneurship, Business and Economics, 2025)
This study aims to examine the impact of earnings management on research analysts' forecast accuracy in Pakistan. The current study collected a sample of 37 non-financial firms listed on the Pakistan Stock Exchange (PSX), containing 407 observations from 2012 to 2022. This study used panel corrected standard error (PCSE) model to get the robust results of the regression model. The results show a significant negative influence of earnings management on research analysts' forecast accuracy in the provided data of Pakistan. These results are in consistent with the existing literature on agency theory. This study is the first to research the research analysts' forecast accuracy in Pakistan. Besides, the first study investigates the influence of earnings management on the accuracy of the research analysts' forecasts. Research Paper Keywords: Research Analysts forecast accuracy, Agency theory, Earnings management, Developing market, Pakistan Reference to this paper should be made as follows: Sajjad, W., Yet, C.E., Hong, M., & Asim, A. (2025). Research Analyst Forecasting Accuracy and Earnings Management: Evidence from Pakistan. Journal of Entrepreneurship, Business and Economics , 13 (1), 102–134.